Efektifitas Pendekatan Psikoterapi Al-Quran dalam Meningkatkan Resiliensi Remaja Pasca Pandemi - Farial Farial; Eka Sri Handayani (Kuras Institute, 2022)
The Covid-19 pandemic that has not been resolved to date has changed human habits, especially in the field of education. One of the most obvious impacts is that students cannot go to school/college as before to prevent the spread of Covid-19. In addition, students are also required to adapt to technology or commonly known as Distance Education (PJJ). The COVID-19 pandemic has become a frightening specter for all people, making all aspects of life different from before some of these problems raise a lot of concerns related to the future of education management and services, the impact of Covid-19 is very influential on the psychology of teenagers. Changes in habits that occurred during the Covid-19 period certainly had an impact on all aspects, both technological adaptation, learning challenges, to the psychology of adolescents as students. Therefore, resilience is needed so that adolescents survive, rise, and adapt to difficult and stressful conditions. in the academic field. The method used in this study is a quantitative method with an experimental research strategy, the subjects in this study are teenagers at MA Muhammadiyah 2 Al-Furqon Banjarmasin in class XI which consists of 3 classes with a total of 99 students in the analysis stage using the T-test technique. For comparative test or difference test. Based on the results of hypothesis testing from both groups using the t-test, it was obtained that tcount = -2,317 and ttable = -1,661. Thus, tcount > ttable with = 5%. The value of tcount is in the rejection area H0, while Ha is accepted, so it can be concluded that there is an effectiveness of giving Al-Quran therapy in increasing post-pandemic adolescent resilience at MA Muhammadiyah 2 Al-Furqon Banjarmasin.